2022
DOI: 10.1002/adem.202200257
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Way Semicrystalline Shape Memory Elastomers: Development and Current Research Trends

Abstract: Two‐way shape memory polymers (SMPs) have gained significant attention in the recent past owing to their ability to spontaneously and reversibly switch between two different shapes when heated and cooled, thereby allowing them to reversibly actuate autonomously. Semicrystalline elastomers are one of the best classes to design two‐way SMPs owing to the crystallization‐induced elongation and the melting‐induced contraction that can result in reversible strain in the elastomeric network and can be applied to fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 151 publications
0
9
0
Order By: Relevance
“…It is well known that the two-way shape change, namely two-way shape memory effect (SME), is the result of the joint action of the switchable phase, the fixation phase, and the internal stress. [24,33,34] According to this basic concept, our twoway shape memory PU was designed by employing the crystalline poly(ε-caprolactone) (PCL) for the switchable phases as well as the covalently cross-linked network as the fixation phase to maintain the structural integration and memorize the permanent polymer network (Figure 1d). Simultaneously, it has been reported that the hydrogen bonds, which abundantly existed throughout any PU network, could serve as the internal stress provider to obtain two-way SME.…”
Section: Fabrication Of Thermal Triggered "On-off" Switchable Tengmentioning
confidence: 99%
“…It is well known that the two-way shape change, namely two-way shape memory effect (SME), is the result of the joint action of the switchable phase, the fixation phase, and the internal stress. [24,33,34] According to this basic concept, our twoway shape memory PU was designed by employing the crystalline poly(ε-caprolactone) (PCL) for the switchable phases as well as the covalently cross-linked network as the fixation phase to maintain the structural integration and memorize the permanent polymer network (Figure 1d). Simultaneously, it has been reported that the hydrogen bonds, which abundantly existed throughout any PU network, could serve as the internal stress provider to obtain two-way SME.…”
Section: Fabrication Of Thermal Triggered "On-off" Switchable Tengmentioning
confidence: 99%
“…A different method employs additive‐crosslinked natural rubber (e.g., fatty acids). stearic acid natural rubber provides a melting/crystallization‐based SME in fatty acids 34 . Polyethers are also employed for switching segments in SMPs because of their low melting points.…”
Section: Design and Mechanism Of Thermo‐ Responsive Shape Memory Beha...mentioning
confidence: 99%
“…33 Elasticity in SMPs provides enhanced physical and chemical crosslinking properties of shape memory effects (SMEs) and is used in engineering applications. 34,35 Materials like physically crosslinked elastomers (PCEs), chemically crosslinked elastomers (CCEs), elastomer blends, and thermoplastic elastomers (TPEs), exhibits elastomeric property and enhances the quality of functional SMPs. 33 The crosslinks in CCEs provide better recovery rates and reliability than other SMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Although various types of 2W-SMPs have been reported in recent years, 23 a very important prerequisite for revealing their potential application values is to identify their response conditions and actuation capacity. 24 Thermomechanical tests are helpful in visualizing 2W-SME; 17 that is, some critical parameters of the 2W-SME can be quantified by studying the individual elongation of the network during the heating–cooling cycle, such as the actuation temperature and reversible strain (Δ ε rev , uniaxial).…”
Section: Introductionmentioning
confidence: 99%
“…22 Thus, the two-way shape memory effect (2W-SME) arises primarily from the thermal crystal transitions (crystallization and melting) of the actuation domains, 17 which are also referred to as crystal-induced elongation (CIE) and melt-induced contraction (MIC). 6 Although various types of 2W-SMPs have been reported in recent years, 23 a very important prerequisite for revealing their potential application values is to identify their response conditions and actuation capacity. 24 Thermomechanical tests are helpful in visualizing 2W-SME; 17 that is, some critical parameters of the 2W-SME can be quantified by studying the individual elongation of the network during the heating-cooling cycle, such as the actuation temperature and reversible strain (De rev , uniaxial).…”
Section: Introductionmentioning
confidence: 99%